Knee and hip osteoarthritis and risk of nine cancers in a large real-world matched cohort study - Turkiewicz, A; Díaz, Y; Duarte-Salles, T; Prieto-Alhambra, D (Oxford University Press, 2021)
Objectives: Joint replacement due to end-stage osteoarthritis (OA) has been linked to incidence of several cancers. We aimed to estimate the association between newly diagnosed knee and hip OA and incidence of nine common cancer types.